Fuzzy-PID controller for an energy efficient personal vehicle: Two-wheel electric skateboard - Bambang Sumantri; Eko Henfri Binugroho; Ilham Mandala Putra; Rika Rokhana (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The two-wheeled electric skateboard (TWS) is designed for a personal vehicle. A Fuzzy-PID control strategy is designed and implemented for controlling its motion. Basically, motions control of the TWS is performed by balancing the pitch position of the TWS. Performance of the designed controller is demonstrated experimentally. The Fuzzy algorithm updates the PID gains and therefore it can handle the changing of the TWS load. Contribution of Fuzzy-PID in reducing the electric energy consumption, which is an important issue in electrical system, is also evaluated. The Fuzzy-PID successes to reduce the electric energy consumption of the TWS compared to the conventional PID.